Creative poster contest: Warna–Warni Malaysia - Mohd Ruslan, Siti Zaharah; Othman, Norlida; Rosli, Nur Aqilah Balqis; Mohd Aris, Nuranis Farhana (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The Creative Poster Contest: Warna–Warni Malaysia, organized by the Cybermath Club at UiTM Negeri Sembilan, Kuala Pilah Campus, was held online from 12 May to 5 June 2025. The competition celebrated creativity, culture, and unity by allowing students to design digital posters that showcased the cultural heritage of their home states. It provided participants with an opportunity to express their creativity, strengthen cultural awareness, and enhance their digital design skills while promoting pride in Malaysia’s diverse cultural identity.